Analysis of the Effectiveness of Garlic (Allium sativum) and Turmeric (Curcuma longa) Extracts as Antifungal Agents Against Candida albicans: Constraints and Inhibiting Factors - Maria Indriani Bupu; Sri Martuti; Monika Putri Solikah (BIOSAINSTEK, 2025)
Candidiasis is an infection caused by the fungus Candida albicans and can attack various parts of the body such as skin, hair, nails, mucous membranes, and internal organs. The use of synthetic antifungal drugs is common in treating this infection, but causes unwanted side effects, therefore alternative treatments based on natural ingredients are needed that are safer and more effective. Garlic (Allium sativum) and turmeric (Curcuma longa) contain bioactive compounds such as allicin and curcumin which have the potential as antifungal agents. The purpose of this study was to determine the effectiveness of garlic (Allium sativum) and turmeric (Curcuma longa) extracts in inhibiting Candida albicans fungus. This study used 3 treatment groups, namely the control group, the garlic (Allium sativum) and turmeric (Curcuma longa) groups with each extract concentration of 20%, 40%, 60% and 80% with six repetitions. Extraction using maceration method with 96% ethanol solvent, while antifungal activity test was conducted using disc diffusion method on Sabouraud Dextrose Agar (SDA) media. Inhibition zone was observed after incubation for 24 hours in an incubator with a temperature of 37 °C. The results showed that garlic and turmeric extracts did not produce inhibition zone against Candida albicans growth. This ineffectiveness was caused by several factors, including the processing of materials, the use of high concentration ethanol solvent, testing method, and the absence of quantitative analysis of active compound content. These factors affect the decrease in the effectiveness of active compounds in the extract, so that it is unable to inhibit the growth of Candida albicans.